Experimental Investigation on Construction of Masonry wall with Crumb Rubber Concrete Blocks. Issue 1 (April 2021) - Gopalakrishnan, Preethi; Joshi, Nikhil N; Gokulraj, R
Abstract: Waste Management is a challenging task in most developing countries. In India, researches are made to minimize waste generation and also also to reuse or recycle waste in all possible ways. (1) Rubber waste is produced equal to plastic waste in India and contributes 10-12% in total waste generation. Industries manufacturing tyres generate more rubber waste followed by the disposal yards dealing with rubber scarp. (2) Among the building materials concrete has a long life span and therefore Crumb Rubber Concrete(CRC) is proven research for rubber waste management for its flexural property. This paper explains the experimental study made for the construction of a masonry wall using crumb rubber concrete with the replacement of fine aggregate with crumb rubber.(3) The results show that Crumb Rubber Concrete would be the best choice for the construction of non-load bearing structures with 20% replacement of Fine aggregate with crumb rubber.